Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3329/bjms.v18i3.41635
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research of Harmine hydrochloride effect on internal organs

Abstract: Objective. The purpose of thisstudy was to determine the chronic toxicity of the drug “Harmine hydrochloride, capsules” for preclinical evaluation of its safety. Materials and methods.The experiment was performed on 48 CD-1 rats. Harmine hydrochloride was injectedto the animals intragastrically at doses of 2.5 mg / kg/per day, 5 mg / kg/per day, 9 mg / kg/per day, 10 mg / kg/per day for 3 months. After 3 months, the animals were withdrew from the experiment, internal organs (brain, heart, spleen, adrenal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Studies of harmine hydrochloride pharmacological activity show edits potential antiparkinsonian activity . Further toxicological studies showed that harmine hydrochloride had no toxic effects on the internal organs or brain in a chronic three-month experiment in rats at the studied doses of 2.5 and 5 mg/kg (Lou et al, 2017;Zhanaidarova et al, 2019;Cui et al, 2019b;Krüzselyi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of harmine hydrochloride pharmacological activity show edits potential antiparkinsonian activity . Further toxicological studies showed that harmine hydrochloride had no toxic effects on the internal organs or brain in a chronic three-month experiment in rats at the studied doses of 2.5 and 5 mg/kg (Lou et al, 2017;Zhanaidarova et al, 2019;Cui et al, 2019b;Krüzselyi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%